Pengaruh CR, DAR dan DER Terhadap Harga Saham pada Perusahaan Sub Sektor Pertambangan Batubara yang Terdaftar di BEI - Hery Koeshardjono; Wahyuni Wulandari; Tatik Amani (CV. Ulil Albab Corp, 2024)
This study observes coal mining sub-sector companies listed on the Indonesia Stock Exchange in 2020 – 2022 to determine how much influence the CR, DAR and DER variables partially and simultaneously have on stock prices. CR, DAR and DER are variables in the associative quantitative research design. To see how much influence it has on stock prices partially is evidenced by the t-count value> t-table and simultaneously is evidenced by the F-count value> F-table with a significance level of 0.05. The sample used was 24 companies that had been observed for three years. The data used in this study came from https://lembarsaham.com and www.idx.co.id. Based on the results of the study, the Current Ratio variable has a significant effect on stock prices, Debt to Asset Ratio has a negative and insignificant effect on stock prices and Debt to Equity Ratio has a negative and significant effect on stock prices. The CR, DAR and DER factors simultaneously have a significant effect on stock value. For the period 2020 – 2022, of the three variables, the Current Ratio variable has the greatest influence on the share prices of coal mining sub-sector businesses listed on the IDX